A critical review on VOCs adsorption by different porous materials: Species, mechanisms and modification methods - Zhu, Lingli; Shen, Dekui; Luo, Kai Hong (Journal of hazardous materials, 2020)
[Display omitted] •Typical porous materials for VOCs adsorption were carefully overviewed.•Adsorption mechanism was intensively discussed between adsorbate and adsorbent.•Different modification technologies were introduced for enhancing VOCs adsorption. Volatile organic compounds (VOCs) have attracted world-wide attention regarding their serious hazards on ecological environment and human health. Industrial processes such as fossil fuel combustion, petrochemicals, painting, coatings, pesticides, plastics, contributed to the large proportion of anthropogenic VOCs emission. Destructive methods (catalysis oxidation and biofiltration) and recovery methods (absorption, adsorption, condensation and membrane separation) have been developed for VOCs removal. Adsorption is established as one of the most promising strategies for VOCs abatement thanks to its characteristics of cost-effectiveness, simplicity and low energy consumption. The prominent progress in VOCs adsorption by different kinds of porous materials (such as carbon-based materials, oxygen-contained materials, organic polymers and composites is carefully summarized in this work, concerning the mechanism of adsorbate-adsorbent interactions, modification methods for the mentioned porous materials, and enhancement of VOCs adsorption capacity. This overview is to provide a comprehensive understanding of VOCs adsorption mechanisms and up-to-date progress of modification technologies for different porous materials.